Müctehidin yokluğunda fıkhî ahkâm: Cüveynî'nin el-Gıyâsî'deki farazî dünyası - (:unkn) unknown (My University, 2012)
İctihad, yaşanan olaylara şer î çözümler bulmanın canlı bir yolu olduğundan herhangi bir zaman diliminin müctehidsiz kalmasının caiz olup olmadığı ve ictihad kapısının kapanıp kapanmadığı gibi tartışmalar fıkıh tarihi boyunca canlılığını hep sürdürmüştür. Bu makalede, ilk olarak, ahkâm-ı sultaniye türü bir eser olan Cüveynînin el-Gıyâsîsi çerçevesinde, sahabeden itibaren şer î hükümleri temel kaynaklardan elde ederek insanlara anlatan fakihlerin farklı dönemlerdeki özellikleri, fukaha arasındaki devamlılık, önceki fukahanın görüşlerinin sonrakilerce anlaşılıp benimsenmesi, zamanın değişmesiyle ortaya çıkan yeni meselelerin nasıl hükme bağlanacağı gibi konular ele alınacak, ardından ictihad ehliyetini haiz müftilerin ve mezhep görüşlerini aktaracak insanların ortadan kalkması ve nihayetinde dinî hükümlerin bütünüyle bilinemez hale gelmesi durumunda takip edilmesi gereken usule dair Cüveynînin önerileri incelenecektir.

Because the ijtihad is a dynamic tool for finding sharia-based solutions to emerging problems, the debates over whether it is permissible for a given era to be devoid of a mujtahid and over whether the gate of ijtihad is closed have always remained vibrant throughout the history of the fiqh. This article will examine Juwaynî s al-Ghiyâthî, a work on al- Ahkâm al-Sultâniyya (the Rules of Government), in order to discuss his perspective on the changing characteristics of the jurists (fuqahâ), who had derived the sharia rulings from the essential Islamic sources and transmitted them to the general public since the time of the Companions, and his take on the imaginary situation of the absence of the fuqaha in society. Within this framework, the article will first discuss Juwaynî s views on the continuity between different generations of the fuqaha, how the earlier jurists views were understood and received by the later generations, and how the new rulings would be applied to the new questions that emerge with the passage of time. The article will then examine Juwaynî s proposals on the method to be applied in case when the muftis with a license for the ijtihad and the ulema who are able to transmit the particular views of madhabs disappear, and therefore religious rulings might be completely unknown to the general public.
Legal ruling in the absence of the mujtahid: Juwaynî s ımaginary world in al-Ghiyâthî